Healthcare Resource Utilization and Costs Related to Falls and Fractures Among People With Type 2 Diabetes Receiving Basal Insulin: The FRAGILE Study - Guillermo E. Umpierrez; Elizabeth K. Pogge; Xuan Li; Ronald Preblick; Jasvinder Gill; Naushira Pandya (Journal of Health Economics and Outcomes Research, 2025)
# Background The association between falls or fall-related fractures and hypoglycemia in people with type 2 diabetes is well established. Insulin treatment is associated with an increased risk of hypoglycemia, which is compounded in people of older age, but the risk is lower with longer-acting vs intermediate- or long-acting basal insulin analogs.